Early experience and the life path - Clarke, Ann M. (Ann Margaret) (J. Kingsley, 2000)
This important book challenges the widely held assumption that early experience has a disproportionate effect on later development. Drawing from over forty years of rigorous empirical research and theoretical enquiry, Ann and Alan Clarke argue that the effects of early experiences are just the first steps in an ongoing and complex life path, on which the shaping or re-shaping of development can occur in any period. The evidence they present for the resilience of children and the interaction of early and subsequent experience clarifies and advances the ancient nature-nurture debate. This debate underpins current developments and approaches in fields as diverse as education, psychology, social care and sociology. The Clarkes' findings have enormous practical implications for professionals working with disadvantaged children and adults. They show the value of interventions with and outside the family, and the potential for positive environments to create lasting change at any stage of life. Early Experience and the Life Path will illuminate the practice of psychologists, psychiatrists, social care professionals and teachers, and anyone working with children who have experience of adversity.